The Role of Item-Specific Information for the Retrieval Awareness of Performed Actions - Li, Guangzheng; Wang, Lijuan (Frontiers in Psychology, 2018)
The research of action memory has lasted for more than thirty years, but it is still unclear that what drives the recollection process of performed actions. In this study, we used remember/know paradigm and designed two experiments to examine the relation between item-specific processing and retrieval awareness of subject-performed task (SPT). The results showed that SPT allows remember responses in remember/know judgments more easily, that is, SPT is more frequently associated with a feeling of re-experiencing the original performed actions. Item-specific processing can improve memory performance and proportion of remember judgments of verbal task (VT), but it does not improve the memory performance and proportion of remember judgments of SPT, indicating that SPT can enhance the item-specific processing, which leads to more remember responses in judgment. The relation between item-specific processing and retrieval awareness of SPT was discussed.